2022
DOI: 10.1093/cercor/bhac447
|View full text |Cite
|
Sign up to set email alerts
|

The left inferior frontal gyrus is causally linked to vocal feedback control: evidence from high-definition transcranial alternating current stimulation

Abstract: Current models of speech motor control propose a role for the left inferior frontal gyrus (IFG) in feedforward control of speech production. There is evidence, however, that has implicated the functional relevance of the left IFG for the neuromotor processing of vocal feedback errors. The present event-related potential (ERP) study examined whether the left IFG is causally linked to auditory feedback control of vocal production with high-definition transcranial alternating current stimulation (HD-tACS). After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…In the non-speaking mouse, homologous higher-order motor regions are recognized for their causal role in the flexible updating of motor plans subsequent to sensory feedback ( Barthas & Kwan, 2017 ; Gremel & Costa, 2013 ). Causal evidence in humans is rare, but a recent study identified greater behavioral compensation and enhanced neural responses to artificially-altered pitch feedback as an after-effect of transcranial alternating current stimulation over the left inferior frontal gyrus ( Li et al, 2023 ). Together, these lines of evidence suggest that the motor-planning regions that create the efferent prediction are integral to performing the correction when that prediction is violated.…”
Section: Discussionmentioning
confidence: 99%
“…In the non-speaking mouse, homologous higher-order motor regions are recognized for their causal role in the flexible updating of motor plans subsequent to sensory feedback ( Barthas & Kwan, 2017 ; Gremel & Costa, 2013 ). Causal evidence in humans is rare, but a recent study identified greater behavioral compensation and enhanced neural responses to artificially-altered pitch feedback as an after-effect of transcranial alternating current stimulation over the left inferior frontal gyrus ( Li et al, 2023 ). Together, these lines of evidence suggest that the motor-planning regions that create the efferent prediction are integral to performing the correction when that prediction is violated.…”
Section: Discussionmentioning
confidence: 99%
“…In the non-speaking mouse, homologous higher-order motor regions are recognized for their causal role in the flexible updating of motor plans subsequent to sensory feedback (Gremel & Costa, 2013; Barthas & Kwan, 2017). Causal evidence in humans is rare, but a recent study identified greater behavioral compensation and enhanced neural responses to artificially-altered pitch feedback as an after-effect of transcranial alternating current stimulation over the left inferior frontal gyrus (Li et al, 2023). Together, these lines of evidence suggest that the motor-planning regions that create the efferent prediction are integral to performing the correction when that prediction is violated.…”
Section: Discussionmentioning
confidence: 99%
“…Altering the function of left DLPFC, either by disrupting or enhancing it, can result in impairment or enhancement of this top–down inhibitory control, which regulates the extent to which feedback perturbations influence speech production. The involvement of left inferior frontal gyrus (IFG) and supplementary motor cortex (SMA) in pitch compensation in Mandarin speakers have also been demonstrated in studies of Dai et al (2022) and Li et al (2023) , in which enhanced or reduced compensatory responses to pitch perturbation were observed after transcranial alternating current stimulation (tACS) over left IFG or cTBS over left SMA, respectively.…”
Section: Neurobiology Findingsmentioning
confidence: 90%